Analisis Value Engineering Produksi Kursi Roda - Fadli, Muhammad; Makmuri, M. Kumroni Makmuri 2 (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
A wheelchair is a tool used to increase mobility abilities for people who have disabilities, such as people with physical disabilities (especially people with leg disabilities), hospital patients who are not allowed to do a lot of physical activity, the elderly, the elderly, and people who have a high risk of injury when walking alone (Wakhid, 2011). According to the English Wheelchair Guidelines, wheelchairs are one of the most commonly used assistive devices to improve personal mobility. About 10% of the global population, namely about 650 million people suffer from disabilities. Of this number, about 10% require a wheelchair. So, it is estimated that around 1% of the total disabled population requires a wheelchair, which is around 65 million people worldwide (English Wheelchair Guidelines, 2007). In Indonesia itself, the Indonesian Ministry of Health (2014) stated that the percentage of people with disabilities who experience limitations in walking or climbing stairs is 10.26% of the total number of people with disabilities in Indonesia. Currently, the availability of wheelchairs that meet ISO standards is still very limited. This is because the selling price of standard wheelchairs is quite expensive so they cannot compete in the commercial market. The availability of standard wheelchairs is dominated by the European and American markets. The price of a standard wheelchair ranges from IDR 2,400,000 to IDR 3,200,000. In Indonesia itself, wheelchairs on the market are dominated by imported products from China and several domestic manufacturers. Imported wheelchairs from China are set at quite affordable prices, namely around IDR 950,000 to IDR 1,350,000. Meanwhile, one of the domestic manufacturers that makes wheelchairs is marketing wheelchairs made from stainless steel and steel with a price range of IDR 2,400,000 to IDR 2,600,000. Imported products have a relatively low selling price because the frame material is used is chrome plated steel. In addition, wheelchairs produced in China do not yet comply with ISO 7176-5:. Of the 2 brands of wheelchairs observed, several parts did not meet ISO 7176-5 specifications, including seat plane angle; effective seat depth; seat surface height at front edge and back support angle. Apart from that, based on observations, there are several shortcomings found in wheelchairs, namely the frame is too heavy, makingoperating the wheelchair difficult; armrest height that is too high from the seat so that the user feels tired when operating the wheelchair; and the distance between the castor and rear wheel is too close, causing reduced wheelchair stability.